Penerapan Asesmen Anggota Polri untuk Penempatan Jabatan di Lingkungan Polda Sumatera Barat - Salmi Wahyuni, Nada; Magriasti, Lince (Policy, Law and Political Research Center, 2024)
This study aims to analyze the implementation of the assessment of Polri members in supporting the proper placement of positions at the West Sumatra Regional Police, as well as identify factors that influence the implementation of the assessment. This research uses a descriptive qualitative method with data collection through interviews and documentation. The results show that the assessment results only serve as recommendations and are not the primary determinant in job placement. The subjectivity of the leadership is more dominant in making decisions on the placement of Polri Officers at Polda West Sumatera compared to the assessment results. The qualitative nature of the assessment means that the ranking of assessment results cannot be determined. Factors affecting the application of the assessment include administrative barriers, such as education, relevant work experience, licenses, and test scores. While these requirements are necessary for police officers who pass the assessment, the assessment results are not the primary determinant of job placement. Leadership policies and organizational culture also significantly influence career development and job placement at Polda West Sumatera. In addition, implementing assessment centers is often ineffective due to scheduling issues that frequently collide.